Tinjauan Historis dan Proliferasi dalam Kajian Komunikasi Pembangunan Kontemporer - Mauliansyah, Fiandy (Universitas Brawijaya, 2020)
Research on the use of ICTs for international development, or information and communication technology for development (ICT4D) research, has a history going back some 30 years. The purpose of this paper is to take stock of the ICT4D research field at this important juncture in time, when ICTs are increasingly pervasive and many different disciplines are involved in researching the area. The paper first provides some reflections on the history of the field broken down into three phases from the mid-1980s to the present day. This is followed by a detailed discussion of future research agenda, including topic selection, and the role of theory. ICT4D research started largely in the academic field of information systems but it is concluded that the future lies in a multidisciplinary interaction between researchers, practitioners, and policy-makers.